THE USE OF VISUAL IMAGERY STRATEGY TO IMPROVE THE STUDENTS’ WRITING SKIL OF RECOUNT TEXT AT THE TENTH GRADE OF SENIOR HIGH SCHOOL - Marpaung, Siti Andrianti (BRIGHT VISION Journal of Language and Education, 2021)
This research aimed to determinet he impac to fusing Visual Imagery strategies in improving the students' writing skils. The subjects of this research were the students of class X MA. Laboratory. UINSU Medan for the 2020/2021 academic year, which consists of 40 students. This research was conducted using a class room action research using two cycles. Each cycle consists of planning, acting,  observing, and reflecting. The data obtained through quantitative and qualitative data. The quantitative data were obtained from tests which included pre-test, post-test I, and post-test I. Meanwhile, the qualitatived at a were obtained from interview sand observation sheets. The results of the data analysis showed that the rewasan  improvement son student writing achievements frome achcycle. This can be seen fromthe mean score of students in the pre-test 50.85 increased to 69.4 in the post-test I an dincreased to 79.3 in the post-test I. In the pre-test, 10% (4 of 40 students) scored >75. In the post-test I the rewere 55% (22 of 44 students) who scored >75. In the second post-test, the rewere 90% (36 of 40 students) whogeta value>75. To test the hypothesis using thet-test formula, the results of thet-test obtainedt  observation (8.60) >t table (1.684). Thus, the alternative hypothesis(Hα) can be accepted. Based on the sefindings, the alternative hypothesis (Hα) states that the use of visual imagery strategies can improve students' ability to writer ecount text. Keywords: Visual Imagery Strategy, Writing, Recount Text, Classroom Action Research